Teoria do desenvolvimento cognitivo de Piaget e sua interface com a terapia cognitivo-comportamental familiar - Melo, Tatiane Coutinho Vieira de (2011)
This paper is a theoretical exercise, which focuses on the interface between Piagetian Theory and the Cognitive-Behavioral Family Therapy, with the proposal to extend the work of Piaget to the field of psychotherapy. To do so, we used the Piaget\'s developmental theoretical perspective, to establish relationships between notions of the cognitive approach and information processing. Besides, it was emphasized setbacks in cognitive stages, which some adults may have in the context of family conflict and were pointed to relations between maladaptive patterns of cognition and this retrogression of cognitive abilities. We also analyzed the cognitive processing that involves those concepts of balancing, accommodation and assimilation - that are mechanisms of regulation and adaptability that seem to underly a possible model of formation of beliefs and schemas. Also, we focused to the principles concerning the Piagetian stages of emotional and moral development, considering that the cognitive and affective aspects permeate the individual\'s moral development. Thus, the aim of this study was to provide to family therapists a theoretical apparatus (the Piagetian theory) to understand the psychopathology from the point of view the setbacks of cognitive abilities of family members when they are in conflict. Finally, we sought to further expand the knowledge which provides a more comprehensive and effective to consider the cognitive and affective course of all family members.